MENGELOLA SUMBER DAYA MILIK BERSAMA UNTUK PEMBERDAYAAN MASYARAKAT MENGGUNAKAN PENDEKATAN “HYBRID INSTITUTIONS”: BUM DESA - Sidik, Fajar; Nasution, Fatih Gama Abisono; Herawati, Herawati (Sosio Konsepsia, 2018)
Abstract                                                                This study aims to explore on the one of best Village Enterprise (BUM Desa) in managing and in utilizing the benefit from natural pool as the tourism destination to village empowerment in Ponggok Village, Klaten Regency. The background this study is started from the problem of the increasing number of BUM Desa significantly after the policy of Law Number 6/2014 about Village is set, however, only a few are considered capable of active and productive. Then, this problem is understood as the using of conceptual theory of hybrid institutions. The research approach is qualitative with case study method is used to explore problems in the field. Interview, observation and documentation techniques are used to collect primary and secondary data during the process of exploration activities. We have analyzed secondary and primary data using qualitative data analysis steps according to Miles and Huberman. The finding from our research shows that  we are succeed in conceptualizing the model and explaining the working mechanism of BUM Desa as hybrid institutions in managing and utilizingof the financial beneficiaries from the natural pool for village empowerment according to the version of Ponggok Village Government. Keywords: village, common pool resource, the village of nature tourism, village-owned enterprise (BUM Desa), hybrid institutions, village empowerment, ponggok village, klaten regency